How far have we come in reducing health disparities? : progress since 2000 : workshop summary - Anderson, Karen M. (Online access: NCBI NCBI Bookshelf., 2012)
On April 8, 2010, the Institute of Medicine's (IOM's) Roundtable on the Promotion of Health Equity and the Elimination of Health Disparities sponsored a public workshop to focus on what, if any, progress has been made to address health disparities. The workshop had three major objectives: first, to assess the progress that has been made; second, to consider the scope and effectiveness of efforts to address the social determinants of health disparities; and third, to determine what still needs to be elucidated about efforts to address social determinants and reduce health disparities. The workshop, Ten Years Later: How Far Have We Come in Reducing Health Disparities?, was organized to further advance the dialogue about health disparities by facilitation of a discussion of the topic among stakeholders, including members of the community, academia, the health care community, and business; policy makers; and philanthropic organizations. The goal of the meeting was to consider the progress--or lack thereof--that has been made over the past decade to reduce health disparities. The workshop also highlighted federal, state, and local efforts to reduce health disparities.